Exploring brucine alkaloid: A comprehensive review on pharmacology, therapeutic applications, toxicity, extraction and purification techniques - Bargee Jain; Nancy Jain; Sourabh Jain; Parusu Kavya Teja; Siddheshwar K. Chauthe; Aakanchha Jain (Elsevier, 2023)
Background: Brucine is derived from the plant Strychnos nux-vomica of the Loganiaceae family, is an indole alkaloid with significant versatility and value. It is considered the most potent and active compound found in Nux-vomica. Brucine exhibits a diverse range of pharmacological and therapeutic effects, encompassing anti-inflammatory, analgesic, anti-tumor, anti-pathogenic, and anti-bacterial properties. Additionally, it influences the cardiovascular system and aids in immune system regulation. Purpose: This review paper aims to provide a comprehensive summary of the extraction, isolation, and purification processes associated with brucine. Additionally, it examines the chemistry, bioactivity, pharmacological, and therapeutic properties of brucine and its derivatives. Furthermore, the toxicological aspects of brucine are also outlined in this review. Study design: This review was prepared based on the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Methods: The data provided in this review article is taken from various research articles from reputed journals, text books, reviews, reference books, and patents published on brucine till date (2023) using electronic search tools such as ScienceDirect, Sci-Finder, Elsevier, Google Scholar, PubMed, ACS, and Web of Science. Results: Despite the extensive therapeutic activities associated with brucine, its clinical application is restricted due to its potential for central nervous system toxicity. However, it has demonstrated utility in the treatment of various surgical peripheral diseases, including rheumatism, dementia, orthopedic conditions, and retinopathy. Further research on brucine is necessary to enhance our understanding, to improve its efficacy, to ensure its safety and thereby reducing its toxicity and expanding its potential for clinical use. Conclusion: In conclusion, brucine is a potent compound with numerous pharmacological and therapeutical values. It has structural resemblance to strychnine and it has potent activity against cancerous cell, inflammatory mediators, and bacterial cells. Despite the fact that it possess wide pharmacological activities, it is also considered to be toxic compound, this can be overcome by novel targeted drug delivery system which can reduce the risk of toxicity and enhance the efficacy. However, brucine has very impressive pre-clinical profile, still many measures are required to make it available to clinical applications with all the safety, effectiveness and efficacy.